First report on spinal hyperbaric opioids in horses - Polydoro,Alexandre da Silva (2006)
This study is the first to report the use of spinal hyperbaric opioids in horses injected through a lumbar-sacral subarachnoid catheter. The injection of hyperbaric subarachnoid morphine and methadone produced short term intense analgesia over the dermatomes of the perineal, sacral, lumbar, and thoracic areas without cardiorespiratory depression, ataxia or central nervous system excitement. The technique involves the use of 10% dextrose as a hyperbaric solvent producing an average hyperbaric solution with a specific gravity of 1030. The use of spinal hyperbaric opioids in horses can be recommended for short term moderate to severe pain management in this species.